Dry gardens. Surrounding the gardens in arid areas - Mulè, Cinzia (2019)
At the current bioclimatic change and shortage of water in which are located some geographical areas, it has become essential reprogram and project a lot of green areas in general and private use. For ages, these have been planned on a garden scheme not appropriate to local conditions. In general, it is discussed the concept of “grass” as a fundamental surface and unifying of the urban landscape. This implies reprogram the concept of “garden” and use of itself, even in many situations may result difficult for the user to understand, and others situations such as in California is the only solution by law. For many people, the problem does not prevail until they realized the high maintenance expenses, and in the case of public areas, these end up in a state of total abandonment as a result of the lack of maintenance. It is relevant to become more aware about the problem, as well as understand that there are solutions too. The crucial thing, as in everything, is study the problem, the economic environment, and the accessible budget to do the best project with balanced costs and benefits to all the community, not only a user.